هوية الأدب الجزائري المكتوب باللغة الفرنسية - سبيعي, حكيمة (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
يهدف هذا المقال إلى رصد أهم العوامل المؤدية إلى تفشي ظاهرة الكتابة باللغة الفرنسية رغم أن الاستعمار قد ولى وانتهى، كما يبين هوية الأدب الجزائري المكتوب باللغة الفرنسية. ولقد لعبت الثورة دورا كبيرا في حياة الشعب الجزائري، وشملت العديد من مجالات الحياة، وقام بها الشعب الجزائري رغبة وإصرار منه لطرد المستعمر، وذلك من أجل التغير والخروج من الظلام الذي فرضته فرنسا عليه، فكانت الثورة بذلك صراع مستمر من أجل الحرية، والمطالبة بالحقوق الإنسانية، وكان ثمن ذلك موت الآلاف الشهداء، وكان العزم موجودا في روح كل جزائري حيث حقق به انتصارات عظيمة، فالتغيير كان تغييرا جذريا شاملا في جميع الميادين   This article aims to monitor the most important factors leading to the spread of the phenomenon of writing in French, despite the fact that colonialism is over and over. I've played the revolution a major role in the life of the Algerian people, and included many areas of life, and carried out by the Algerian people's desire and determination it to expel the colonizer, in order to change and get out of the darkness imposed by France upon, was the revolution that constant struggle for freedom, and to demand human rights, and the price of it was the death of thousands of martyrs, and it was determined spirit is present in all Algerian, where it has achieved great victories, change has been a radical change in a comprehensive all fields.